2019
DOI: 10.3390/ijerph16173104
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk in Non-Alcoholic Fatty Liver Disease: Mechanisms and Therapeutic Implications

Abstract: New evidence suggests that non-alcoholic fatty liver disease (NAFLD) has a strong multifaceted relationship with diabetes and metabolic syndrome, and is associated with increased risk of cardiovascular events, regardless of traditional risk factors, such as hypertension, diabetes, dyslipidemia, and obesity. Given the pandemic-level rise of NAFLD—in parallel with the increasing prevalence of obesity and other components of the metabolic syndrome—and its association with poor cardiovascular outcomes, the questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
0
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(135 citation statements)
references
References 137 publications
(141 reference statements)
0
106
0
15
Order By: Relevance
“…The precise mechanisms linking NAFLD with cardiac complications are poorly understood. However, several pathophysiological mechanisms have been postulated to be involved such as insulin resistance, visceral adiposity, subclinical inflammation, dyslipidemia, and oxidative stress (Figure 1e) [96].…”
Section: Mechanisms Linking Cardiac Disorders To Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise mechanisms linking NAFLD with cardiac complications are poorly understood. However, several pathophysiological mechanisms have been postulated to be involved such as insulin resistance, visceral adiposity, subclinical inflammation, dyslipidemia, and oxidative stress (Figure 1e) [96].…”
Section: Mechanisms Linking Cardiac Disorders To Nafldmentioning
confidence: 99%
“…Bariatric surgery represents a recommended choice for morbidly obese individualsif lifestyle modifications and pharmacological approach have not yielded long-term success. It provides cardiovascular benefits in terms of reducing overall mortality by improving hepatic inflammation, metabolic syndrome components, and cardiac morphology [96,117].…”
Section: Managementmentioning
confidence: 99%
“…Beyond its inherent liverrelated morbidity and mortality, NAFLD also has a strong mutual, bi-directional relationship with type 2 diabetes (T2D)/metabolic syndrome (MetS) [40,41]. Moreover, it is associated with an increased incidence and prevalence of fatal and non-fatal cardiovascular disease (CVD) events, mainly coronary heart disease (CHD), independently of classical cardiovascular risk factors [42][43][44][45]. Interestingly, several observational studies reported an association between NAFLD and increased risk of AF in patients with and without T2D, after adjustment for multiple potential confounders [46].…”
Section: Af and Vte In The Nafld Spectrummentioning
confidence: 99%
“…Bei Männern stellt sie nach der ASH die zweithäufigste Ursache dar [14]. Darüber hinaus haben Studien wiederholt gezeigt, dass die NASH als unabhängiger Risikofaktor für kardiovaskuläre Ereignisse gilt und diese zugleich die häufigste Todesursache bei Patienten mit NAFLD ist [15,16]. NAFLD-Patienten haben zudem ein erhöhtes Risiko, ein extrahepatisches Karzinom (v.a.…”
Section: Klinik Und Relevanzunclassified